2006
DOI: 10.1097/01.mrr.0000210048.09668.ab
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward people with disabilities: a comparison between health care professionals and students

Abstract: The objective of this study was to explore the attitudes of health care professionals and their students towards people in Hong Kong with disabilities. The attitudes of four groups of professionals and students (physiotherapists, occupational therapists, social workers and nurses) were assessed using the well-documented Attitude Toward Disabled Persons scale through the methodology of mailed questionnaires. Comparisons were made among different groups of students and professionals in order to gain insight into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
48
2
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 8 publications
11
48
2
13
Order By: Relevance
“…The attitudes of physiotherapists, occupational therapists, social workers, and nurses in Hong Kong were assessed utilizing the Attitudes Towards Disabled Persons (ATDP) scale form O [35,36]. The goal of this research was to compare healthcare students and practicing professionals in the groups described above.…”
Section: Attitudes Of Physicians Nurses and Therapistsmentioning
confidence: 99%
“…The attitudes of physiotherapists, occupational therapists, social workers, and nurses in Hong Kong were assessed utilizing the Attitudes Towards Disabled Persons (ATDP) scale form O [35,36]. The goal of this research was to compare healthcare students and practicing professionals in the groups described above.…”
Section: Attitudes Of Physicians Nurses and Therapistsmentioning
confidence: 99%
“…They concur with findings from previous studies that suggest increased contact with people with disability can change physiotherapy student attitudes toward disability. [6][7][8] We found a positive change in attitudes to disability among students who spent a relatively short amount of time (12 hours) working with a young adult with disability. Overall, the average change in students' ratings of discomfort with interacting with people with disability was larger than the average change reported after a 12-week campus-based university curriculum for physiotherapy students focusing on neurological disability.…”
Section: Discussionmentioning
confidence: 72%
“…5 Past studies found that physiotherapy students who had a close family member with a disability, who had prior social contact with people with disabilities, or who had worked with people with disabilities possessed more positive attitudes toward disability than their peers who did not have such experiences. 6,7 Practising physiotherapists have more positive attitudes to disability than physiotherapy students, 8 and physiotherapy students show positive changes in their attitudes toward disability as they progress through their degree, 6,7 which may be explained by their exposure to more opportunities for contact with people with disability. However, increased contact alone may not lead to more positive attitudes.…”
mentioning
confidence: 99%
“…Imajuću to na umu, mnogi istraživači su ispitivali stavove zdravstvenih radnika (ljekara, medicinskih sestara, fizioterapeuta i sl.) prema osobama sa ometenošću [10,13,14]. Ništa manje pažnje se ne posvećuje proučavanju stavova budućih zdravstvenih radnika, tj.…”
Section: Uvodunclassified
“…Druga studija pronalazi da studenti zdravstvenih struka imaju gore stavove od samih zdravstvenih radnika (fizioterapeuta, socijalnih radnika, okupacionih terapeuta i sestara). U istom istraživanju, među zdravstvenim radnicima medicinske sestre pokazuju najnegativnije stavove [13].…”
Section: Uvodunclassified